Efectividad del producto orgánico enerplant en el cultivo del pimiento capsicum annum l en la granja Santa Inés - Maza Maza, Jaime Enrique (2006)
From January to June 2006, was carried out at the Santa Inés farm, located in Machala, El Oro province, an experiment with 3 organic fertilizers in front of an Absolute and a Conventional control. The objectives were: 1. To determine the effectiveness of the organic product Enerplant in a pepper crop (Capsicum annum L.), and 2. To realize an economical analysis of treatments. The used treatments were 1. Enerplant, 2. Strong, 3. Biol, 4. Conventional (urea), and 5. Absolute. The experimental design was a Complete Blocks at random with 5 treatments and 4 replications. In the plant bed the rows were divided according to the products used in each treatment, the variety Long Irazu and the seeding was made to continuous flow, with a wa-tering frequency of 1 to 2 days. The transplant was made to the 36 days. The planting distance was of 0,40 m between plants and 1 m in the furrows. The application of organic products was carried out with the quantity defined in the treatments, the chemical was applied in a half moon pattern 10 cm from the plant, every 10 days starting from the date of transplant. The conclusions were: 1) the heights at the 30, 45 and 60 days they were influenced positively by the Enerplant, and the Strong, increasing them over the check. 2) the days to the bloom-ing were reduced by the action of the organic ones. 3) the number of fruits per plant and the fruit weight were also positively influenced for the organic products. The yield per hectare in kilograms was highly significant. All the organic products are better than the control includ-ed the conventional one. The three organic fertilizers responded better than the absolute one. The best profitability was obtained with Ener-plant, Strong and the Conventional (urea). It is recommended to study in the low areas of El Oro the organic fertilizer, in different dose and application time.